2020
DOI: 10.3390/molecules25163672
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Fibroblast Activation Protein Alpha Expression in a Preclinical Mouse Model of Glioma Using Positron Emission Tomography

Abstract: Glioblastoma multiforme (GBM) is the most aggressive glioma of the primary central nervous system. Due to the lack of effective treatment options, the prognosis for patients remains bleak. Fibroblast activation protein alpha (FAP), a 170 kDa type II transmembrane serine protease was observed to be expressed on glioma cells and within the glioma tumor microenvironment. To understand the utility of targeting FAP in this tumor type, the immuno-PET radiopharmaceutical [89Zr]Zr-Df-Bz-F19 mAb was prepared and Lindmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Glioblastoma multiforme (GBM) is the most aggressive glioma of WHO Grade III and IV. Despite the advances in therapeutics, the prognosis for patients remains poor 24 , 25 . FAP was found to be expressed on glioma cells and tumor stroma especially in proximity to blood vessels 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most aggressive glioma of WHO Grade III and IV. Despite the advances in therapeutics, the prognosis for patients remains poor 24 , 25 . FAP was found to be expressed on glioma cells and tumor stroma especially in proximity to blood vessels 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pandya et al updated the mAb F19 antibody with a desferrioxamine (DFO) chelator for the complexation of the positron emitter 89 Zr, which has a half-life suitable for PET imaging with radiolabeled antibodies [ 11 ].…”
Section: Fap Targeting Compoundsmentioning
confidence: 99%
“…Due to the unique overexpression and membrane localization of FAP on various cells within the GBM microenvironment, FAP is considered a potential molecular diagnostic biomarker, and FAP inhibitors (FAPIs) have been under investigation for PET imaging in several cancers [ 78 ], broadening the applications for noninvasive tumor diagnosis, grading stratification and planning for surgery and radiotherapy. Both biodistribution studies in U87MG tumor-bearing murine models and small animal PET studies have shown increased immuno-PET radiotracer retention in tumors over time, and the accumulation of radiotracers was a specific marker of FAP expression, indicating that FAP might be a potential imaging biomarker for GBM diagnosis [ 11 ]. Recently, the first in-human clinical pilot study utilizing 68 Ga-FAPI PET further observed increased tracer uptake in IDH-wildtype and IDH-mutant GBM and WHO grade III IDH-mutant astrocytoma but not in WHO grade II astrocytoma [ 24 ].…”
Section: Future Clinical Applications Of Fapmentioning
confidence: 99%
“…In various malignant tumors, FAP is overexpressed and has been demonstrated to participate in tumor growth and progression; therefore, efforts in the clinical translation of FAP have been made, including imaging biomarkers, prognostic value and FAP-targeted therapies [ 8 ]. Recent studies discovered upregulated FAP expression within the GBM microenvironment [ 9 ] and associated FAP expression with tumorigenesis, immunosuppression and chemoresistance in GBM [ 10 , 11 , 12 ]. As an identifying surface marker of cancer-associated fibroblasts (CAFs) in other solid tumors, FAP also assists CAFs in suppressing antitumor immunity, promoting tumor growth and driving epithelial–mesenchymal transition (EMT) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%